Research on the full-dimensional defined polymorphic smart network - Yuxiang HU; Peng YI; Penghao SUN; Jiangxing WU (Tongxin xuebao)
For current Internet is confronted with some defects such as rigid structure,single IP bearing,and disability in suppressing unknown threats,the functions,performance,efficiency and security of the Internet were promoted from the perspective of network structure,the “structure definition” was introduced through all levels of the Internet,and a network architecture of multi-modal presentation of network functions was provided in all levels:full-dimensional defined polymorphic smart network (PINet),which supported full-dimensional definition and multi-modal presentation of addressing and routing,switching mode,interconnection mode,network element,transmission protocol,service properties and so on.Then the vision and goal,architecture and model,as well as the key technologies of PINet were discussed.The proposed architecture can provide a possible solution to the development of new network technologies.